Open data and smallholder food and nutritional security - Jellema, A.; Meijninger, W.; Addison, Chris (Technical Centre for Agricultural and Rural Cooperation, 2015)
This report was commissioned CTA as a member of the GODAN initiative. It aims to provide a better understanding of the actual impact of the open data movement on the food and nutrition security of smallholders and highlight the areas of potential unfilled opportunity.